Women's voice on changes in childbirth care practices: a qualitative approach to women's experiences in Brazilian private hospitals participating in the Adequate Childbirth Project - Andreza Pereira Rodrigues; Débora Cecília Chaves de Oliveira; Maysa Luduvice Gomes; Lucia Regina de Azevedo Nicida; Jacqueline Alves Torres; Amanda da Trindade Dias Coutinho; Beatriz da Silva Soares de Souza Cravo; Juliana Guimarães Dantas; Thays Basílio Oliveira; Rosa Maria Soares Madeira Domingues (BMC, 2023)
Plain Language Summary In Brazil, childbirth practices are strongly marked by surgical events and particularly in the private sector cesarean sections reach rates above 80%. The Adequate Childbirth Project (PPA) is a quality improvement project developed at Brazilian hospitals with the aim of changing the current model of childbirth care and reducing unnecessary cesarean sections. A qualitative study was developed in order to understand how hospitals have included the participation of women in the PPA. Based on interviews with 102 women, the present study shows that the PPA was unknown to most women before delivery. A polysemy of terms, including adequate childbirth, promotes recognition of the "new" model of care. Visits to the hospital and antenatal care groups for pregnant women are opportunities for contacts that change the perception of what childbirth can be. Women's participation to improve childbirth care is relevant and necessary. The women's voice in the PPA is still incipient and women are not yet included as agents of change, and their voices are silenced. Hospitals and health plan operators should create strategies to engage them. Women's voices may be listened to not only during but also before and after childbirth.